Secured Icmp Based Ip Traceback Scheme To Trace The Spoofed Ip Locations (International Journal of Engineering and Computer Science, 2016)
The Internet Protocol (IP) is the basic protocol for sending data over the Internet and many other computer networks. IP spoofing is the creation of Internet Protocol (IP) packets with a forged source IP address, with the purpose of thrashing the identity of the sender or an attacker can make it appear that the packet was sent by a different machine. The objective of this paper is to devise the passive IP trace back (PIT) scheme using Internet Control Message Protocol(ICMP) to avoid the operational obstacles of IP trace back schemes. PIT investigates ICMP error messages (path backscatter)  triggered by spoofing traffic, and tracks the spoofers based on public available information (eg.topology). This scheme(PIT) discover the spoofers without any operational requirement and exhibits the causes, collection, and the statistical results on path backscatter, demonstrates the processes and effectiveness of PIT, and shows the captured locations of spoofers throughout applying PIT on the path backscatter data set. These results are capable of expose the  spoofed IP locations.